P05 A case of coil-assisted flow diversion using the Neqstent Endosaccular device. (29th August 2022) - Chung, R-E; Qayyum, N; Jadun, CK; Lamin, S; Hashim, Z
Abstract : New endosacculars device including Woven EndoBridge (WEB) and Contour has been developed to address the challenges faced in treating wide neck aneurysm. We report a case of embolization of wide neck MCA aneurysm using the Neqstent endosaccular device. This device is designed to cover the neck adequately while providing a scaffolding for subsequent coiling, and produces a degree of flow diversion, thus reduces the risk of neck recurrence and secondary occlusion of the parent vessel and its branches. Sizing of the device is straightforward requiring only the aneurysm neck, and absence of the need of post-embolization anti-platelet is seen favourable.